Absorption-dependent generation of singlet oxygen from gold bipyramids excited under low power density. Issue 100 (29th October 2015) - Lv, Junliang; Zhang, Xin; Li, Nana; Wang, Baoju; He, Sailing
<x xml:space="preserve">Abstract</x> Gold bipyramid-mediated singlet oxygen generation for photodynamic therapy of cancer cells in the optical biological window.